2018
DOI: 10.1093/her/cyx064
|View full text |Cite
|
Sign up to set email alerts
|

Reducing 30-day readmission rates in a high-risk population using a lay-health worker model in Appalachia Kentucky

Abstract: This exploratory study aimed to address the effectiveness of a lay-health worker (LHW) model in addressing social needs and readmissions of high-risk patients admitted in a rural community hospital. A quasi-experimental study design assessed implementation of a LHW model for assisting high-risk patients with their post-discharge social needs. Outcome measures included 30-day hospital readmissions rates during a 4-month baseline period compared with a 6-month post-implementation period. The LHW intervention inv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 30 publications
0
8
0
Order By: Relevance
“…Transitions-of-care programs that focus on medication management and adherence, potentially utilizing ambulatory care pharmacists or pharmacy technicians, may be a sustainable and cost effective way to ensure appropriate medicine education and follow-up [ 31 ]. The lay healthcare worker model, in which a member of the community who has received training to promote or carry out healthcare services, has also been implemented to assist high-risk patients with post-discharge social needs and has been shown to significantly reduce 30 day hospital readmission rates [ 32 ]. Interdisciplinary care and communication between hospitals, pharmacists, ambulatory providers, social workers, and mental health professionals is necessary in treating patients with complex infections that have barriers to healthcare.…”
Section: Discussionmentioning
confidence: 99%
“…Transitions-of-care programs that focus on medication management and adherence, potentially utilizing ambulatory care pharmacists or pharmacy technicians, may be a sustainable and cost effective way to ensure appropriate medicine education and follow-up [ 31 ]. The lay healthcare worker model, in which a member of the community who has received training to promote or carry out healthcare services, has also been implemented to assist high-risk patients with post-discharge social needs and has been shown to significantly reduce 30 day hospital readmission rates [ 32 ]. Interdisciplinary care and communication between hospitals, pharmacists, ambulatory providers, social workers, and mental health professionals is necessary in treating patients with complex infections that have barriers to healthcare.…”
Section: Discussionmentioning
confidence: 99%
“…Their analysis of data, from 98 hospitals in the State of Washington from 2012 to 2014, indicated that a reduction in acute myocardial infarction (AMI) readmission rates is related with increased operating revenues as expenses associated with costly treatments related with unnecessary readmissions are avoided. Cardarelli et al (2018) carried out a quasi-experimental study design which assessed implementation of a lay0health worker (LHW) model for assisting high-risk patients with their post-discharge social needs. The LHW intervention involved assessment and development of a personalized social needs plan for enrolled patients (e.g.…”
Section: Literature Reviewmentioning
confidence: 99%
“…To the extent that implementation of better serious illness care and reduction in low‐value services yields substantial Medicare savings, part of those savings should be used to expand and retain the coordinated care workforce and to support local systems of social and supportive services . Improving data collection and developing quality measures to determine the added value of community‐based services and team‐based integrated care is necessary for guiding savings into the most needed areas of the workforce …”
Section: Model Requirementsmentioning
confidence: 99%